Monte Carlo simulation of SiPMs with GATE. (1st September 2022) - Mehadji, Brahim; Dupont, Mathieu; Fougeron, Denis; Morel, Christian
Abstract: Silicon photomultipliers (SiPMs) replace photomultiplier tubes (PMTs) for the detection of light in many applications, particularly in high energy physics and medical imaging. We describe a flexible implementation of a SiPM model for the GATE Monte Carlo simulation platform, which is based on the SiPM noise description proposed by Rosado and Hidalgo, and describe an easy and effective method to determine and instantiate the SiPM noise model with simple measurements. We also simulate the micro-cell Single Photon Time Resolution (SPTR) and describe its measurement.